Effect of growth pressure on graphene direct growth on r-plane and c-plane sapphires by low-pressure CVD. (13th December 2018) - Ueda, Yuki; Yamanda, Jumpei; Fujiwara, Kyosuke; Yamamoto, Daichi; Maruyama, Takahiro; Naritsuka, Shigeya
Abstract: Graphene was grown on both r-plane and c-plane sapphires by low-pressure chemical vapor deposition without using a metal catalyst. The growth pressure was systematically changed to investigate how the growth pressure effects the graphene growth. Consequently, it was found that the coverage of the graphene increased with increasing growth pressure on the r-plane sapphire while it decreased with increasing growth pressure on the c-plane sapphire. Raman spectroscopy and atomic force microscopy indicates that the growth layer is single-layer graphene on the r-plane sapphire while it is a bi-layer on the c-plane sapphire. Graphene is thought to grow on the r-plane sapphire simply in a two-dimensional nucleation mode. On the other hand, graphene tends to grow in the pits formed on the surface of the c-plane sapphire. The pits are thought to be produced by the oxygen desorption and have some catalytic effects.